Correlations within the EFQM Business Excellence Model by Applying a Factor Analysis - Nicolae Al. Pop; Corina Pelau (Amfiteatru Economic Journal, 2017)
Specialists in the field of business administration have tried over time to identify those elements or combination of elements which lead to a higher performance and excellence of companies. One of these models was created and it is applied by the European Foundation of Quality Management. This model defines nine elements, divided into enablers and results. Although this model is widely used in the evaluation of businesses, empirically there are still concerns regarding the characterization and correlations between the elements of the model and the connection with the performance of a company. This article aims to determine the correlations between the elements of the EFQM model based on the results of a research conducted in a clothing company in Romania. For this, the factor analysis was applied in order to determine both the correlations between the elements of the model and in order to group them in several strategic directions. Based on the results, there were determined three strategic directions. Out of these directions, one was oriented towards the external environment of the company, one was oriented towards the internal environment and the third one towards the brain of the company, who has the vision and the strategic thinking.
Keywords: M10; M11; M31; 330; business excellence model; EFQM model; factor analysis; performance; correlations; total quality management